Optimizing Diet to Slow CKD Progression - Molina, Pablo; Gavela, Eva; Vizcaíno, Belén; Huarte, Emma; Carrero, Juan Jesús (Frontiers in Medicine, 2021)
Due to the unique role of the kidney in the metabolism of nutrients, patients with chronic kidney disease (CKD) lose the ability to excrete solutes and maintain homeostasis. Nutrient intake modifications and monitoring of nutritional status in this population becomes critical, since it can affect important health outcomes, including progression to kidney failure, quality of life, morbidity, and mortality. Although there are multiple hemodynamic and metabolic factors involved in the progression and prognosis of CKD, nutritional interventions are a central component of the care of patients with non-dialysis CKD and of the prevention of overweight and possible protein energy-wasting. Here, we review the reno-protective effects of diet in adults with non-dialysis CKD stages 3-5, including transplant patients.